2017
DOI: 10.3390/ma10111296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Relative Humidity on Adsorption Breakthrough of CO2 on Activated Carbon Fibers

Abstract: Microporous activated carbon fibers (ACFs) were developed for CO2 capture based on potassium hydroxide (KOH) activation and tetraethylenepentamine (TEPA) amination. The material properties of the modified ACFs were characterized using several techniques. The adsorption breakthrough curves of CO2 were measured and the effect of relative humidity in the carrier gas was determined. The KOH activation at high temperature generated additional pore networks and the intercalation of metallic K into the carbon matrix,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…We observed that the S BET and V total of ANFs were enhanced by either activation time or the quantity of the activation reagent. However, after impregnation with TEPA, the S BET and V total were reduced proportionately, an observation that is consistent with those of other studies [11,14]. In particular, micropores of the chemically activated ANFs undetectable because the percolation of the TEPA solution blocked the tiny pores.…”
Section: Measurement Of Co 2 Adsorption Capacitysupporting
confidence: 90%
See 2 more Smart Citations
“…We observed that the S BET and V total of ANFs were enhanced by either activation time or the quantity of the activation reagent. However, after impregnation with TEPA, the S BET and V total were reduced proportionately, an observation that is consistent with those of other studies [11,14]. In particular, micropores of the chemically activated ANFs undetectable because the percolation of the TEPA solution blocked the tiny pores.…”
Section: Measurement Of Co 2 Adsorption Capacitysupporting
confidence: 90%
“…However, upon the impregnation of TEPA (60-ANF-TEPA), there was a significant increase in the pyridinic and quaternary N-groups, possibly derived from the total conversion of shake-up satellites and adsorbed NO 2 . Such observation which implied that the linear TEPA resulted in the increase of pyridine-like structures or six-member or five-member rings [14]. As expected, HNO 3 oxidation evinced lowering of basic N-groups (pyridines), while the least basic groups (shake-up satellites and adsorbed NO 2 ) were re-introduced to the ANFs.…”
Section: Chemical Properties Of the Anfssupporting
confidence: 56%
See 1 more Smart Citation
“…To summarize how activation by KOH takes place, three main methods take place [16]: 1) Chemical activation which involves redox reactions between Potassium compounds and the carbon material which results in the formation of a porous structure.…”
Section: Activation Mechanismmentioning
confidence: 99%
“…The current CO 2 emission reduction technologies are mainly divided into four ways: pre-combustion decarbonization [2,3], chemical chain circulation [4,5], pure oxygen combustion [6,7], and post-combustion capture [8,9,10,11]. Among them, CO 2 capture and storage (CCS) technology has been widely used [12,13,14,15], but its cost is high [16,17]. However, alkali metal carbonates such as Na 2 CO 3 and K 2 CO 3 have become the promising CO 2 adsorbents due to their low cost, low secondary pollution, and high cycle efficiency [18,19].…”
Section: Introductionmentioning
confidence: 99%